Revisiting the ‘Homeland’ Through a Transnational Lens - Karki, Karun Kishor; KC, Hari (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
In this paper, we bring our individual and collective memories of Nepal to reflect upon how we imagine, remember, and perform the diasporic nationalism while living abroad. We argue that diasporic nationalism is often framed by the homeland's historical dimensions and through an imagined and identificatory relation to the homeland. In doing so, we bring our learning experiences during high school in Nepal and critically zero in on how these curriculums taught us only a single narrative of Nepal-India relation by grossly neglecting the other side of the narrative. To deconstruct such a grand narrative, we critically analyze the other side of the narrative, which reveals the Nepal-India relation as a 'paradox' between closeness and detachment. We discuss cross-border controversies in which the Indian hegemony of perpetuating colonial ideas overpowers Nepal through political and geopolitical intervention. We conclude the paper with our remarks to mitigate animosities and rebuild the fractured relationship between the two nations.